The Local Water Utilities Administration library user needs and patterns of information and library use - Ayson, Raul L. (1994)
This study of the LWUA seeks to determine the information needs and patterns of information and library use of the users. The aims of the study are:1.to determine the information needs of the users; 2. to determine the purposes of the users in using the LWUA library; 3. to know the methods used by the users in doing information research; 4. to determine the factors that affect their use of the LWUA library; 5. to determine the users' personal evaluation of the services, facilities, collection and staff performance; 6. to recommend possible improvements on the existing services of the LWUA library which would hopefully meet the needs of the users.